Seni Musik Hadrah Putri di Pondok Pesantren Al Munawwir Krapyak - ANDRE INDRAWAN; SUSANTI ANDARI; SURYATI - (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
Hadrah Music in Pondok Pesantren Al Munawwir Krapyak. This study investigates an Islamic musical genreknown as the Hadrah, practiced by female students of the Pondok Pesantren (Islamic boarding school) Al Munawwir.It is based on an ethnomusicological fi eld research conducted between May 2007 and September 2008.Thisstudy fi nds that basic song form is exist in the Hadrah’s songs while their lyrics are mostly taken from classical as wellas popular Islamic poem collections. Although the Hadrah song was performed by melodic ornamental improvisationtechniques that normally applied in reciting the Qur’an, the singer always try to follow the Arabic reading rulescarefully. This fi nding has given us an indication that in order to achieve a good result of musical production, aswell, the Hadrah singers have to master not only the art of Holy Qur’an recitation but also Arabic language fl uency.The female Hadrah is normally performed as a religious entertainment in the school’s traditions, such as anniversaryand graduation celebrations.